The anthelmintic efficacy of plant-derived cysteine proteinases against the rodent gastrointestinal nematode, Heligmosomoides polygyrus, in vivo - Stepek, Gillian; Lowe, Ann; Buttle, David J.; Duce, I.R.; Behnke, Jerzy M. (Cambridge University Press, 2007)
Gastrointestinal (GI) nematodes are important disease-causing organisms, controlled primarily through treatment with synthetic drugs, but the efficacy of these drugs has declined due to widespread resistance, and hence new drugs, with different modes of action, are required. Some medicinal plants, used traditionally for the treatment of worm infections, contain cysteine proteinases known to damage worms irreversibly in vitro. Here we (i) confirm that papaya latex has marked efficacy in vivo against the rodent gastrointestinal nematode, Heligmosomoides polygyrus, (ii) demonstrate the dosedependent nature of the activity (>90% reduction in egg output and 80% reduction in worm burden at the highest active enzyme concentration of 133 nmol), (iii) establish unequivocally that it is the cysteine proteinases that are the active principles in vivo (complete inhibition of enzyme activity when pre-incubated with the cysteine proteinase-specific inhibitor, E-64) and (iv) show that activity is confined to worms that are in the intestinal lumen. The mechanism of action was distinct from all current synthetic anthelmintics, and was the same as that in vitro, with the enzymes attacking and digesting the protective cuticle. Treatment had no detectable side-effects on immune cell numbers in the mucosa (there was no difference in the numbers of mast cells and goblet cells between the treated groups) and mucosal architecture (length of intestinal villi). Only the infected and untreated mice had much shorter villi than the other 3 groups, which was a consequence of infection and not treatment. Plant-derived cysteine proteinases are therefore prime candidates for development as novel drugs for the treatment of GI nematode infections.